wireless sensor network clustering based on label propagation algorithm - Monireh Sadat Younespour; Morteza Romoozi (مدیریت مهندسی و رایانش نرم)
Wireless sensor network is a growing technology.  In wireless sensor networks, performance is usually affected by energy constraints. In this paper, a method is proposed based on the label propagation algorithm for this limitation. At first, the sensors are composed of a graph In the next stage weighing the edges of this graph is based on four similarity measure  Then for each node, the centrality and the initial label are obtained And finally, by updating the lebel,nodes with the same label are placed in a cluster The results of the proposed method have been compared with  the number of live nodes and the mean energy of live nodes measures by the leach method The results indicate that in the proposed method of positioning the sensors and setting the threshold value for the formation of the graph from the sensors are only fundamental variables And the comparison shows that the proposed method is superior to the leach method